Risks and Benefits of Discontinuation of Nucleos(t)ide Analogue Treatment: A Treatment Concept for Patients With HBeAg‐Negative Chronic Hepatitis B - Florian vanBömmel; Thomas Berg (Hepatology Communications, 2021)
Systematic discontinuation of long‐term treatment with nucleos(t)ide analogues (NAs) is one strategy to increase functional cure rates in patients with chronic hepatitis B e antigen (HBeAg)–negative hepatitis B. Currently, available study results are heterogeneous; however, long‐term hepatitis B surface antigen (HBsAg) loss rates of up to 20% have been reported in prospective trials. This review proposes criteria that can be used when considering NA discontinuation in patients with chronic hepatitis B virus (HBV). Discontinuing NA treatment frequently results in a virologic and biochemical relapse that runs through different phases: the lag phase, reactivation phase, and consolidation phase. The HBV‐DNA flares observed during the reactivation phase are often transient and most likely represent a trigger for inducing a long‐term immune control by specific CD8+ T cells, and therefore do not need immediate interventions but close follow‐up evaluation. Low HBsAg levels at the time of treatment cessation predict a positive long‐term response to NA discontinuation associated with a higher likelihood of HBsAg clearance. Other host and viral biomarkers are currently under evaluation that may prove to be helpful to further characterize the population that may benefit most from the finite NA treatment concept. Potential harmful biochemical flares during the reactivation phase need to be identified early and can be effectively terminated by reintroducing NA treatment. Hepatic decompensation represents a risk to patients with cirrhosis undergoing NA discontinuation. Therefore, the finite NA approach should only be considered after excluding advanced fibrosis and cirrhosis and if a close follow‐up of the patient and supervision by an experienced physician can be guaranteed. Conclusion: For selected patients, NA discontinuation has become a powerful tool to achieve control over HBeAg‐negative HBV infections. Its significant effect represents a challenge to novel treatment approaches, but it may also serve as their enhancer.